2011
DOI: 10.1182/blood-2010-07-295626
|View full text |Cite
|
Sign up to set email alerts
|

CCR6/CCR10-mediated plasmacytoid dendritic cell recruitment to inflamed epithelia after instruction in lymphoid tissues

Abstract: Absent in peripheral tissues during homeostasis, human plasmacytoid dendritic cells (pDCs) are described in inflamed skin or mucosa. Here, we report that, unlike blood pDCs, a subset of tonsil pDCs express functional CCR6 and CCR10, and their respective ligands CCL20 and CCL27are detected in inflamed epithelia contacting blood dendritic cell antigen 2 ؉ pDCs. Moreover, pDCs are recruited to imiquimod-treated skin tumors in WT but not CCR6-deficient mice, and competitive adoptive transfers reveal that CCR6-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…With respect to potential paracrine effects, CCR6 expression has been reported in various immune cells found within the bone environment, and CCL20 has been shown to stimulate chemotaxis in these cells. (5)(6)(7) Our data indicate that osteoblasts are able to recruit both BMM and T cells, at least in part through CCL20/CCR6 signaling. Given the reported ability of BMM and T cells to promote osteoblast differentiation and survival, (26,29,33) diminished recruitment of these immune cells may also contribute to the observed low-bone phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…With respect to potential paracrine effects, CCR6 expression has been reported in various immune cells found within the bone environment, and CCL20 has been shown to stimulate chemotaxis in these cells. (5)(6)(7) Our data indicate that osteoblasts are able to recruit both BMM and T cells, at least in part through CCL20/CCR6 signaling. Given the reported ability of BMM and T cells to promote osteoblast differentiation and survival, (26,29,33) diminished recruitment of these immune cells may also contribute to the observed low-bone phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…In steady state, PDC reside mainly in T cell-rich areas in lymph nodes and secondary lymphoid organs 7 . Localizations of PDC in other lymphoid organs, such as Peyer’s patches of the gut 22 , and tonsils 23 , have been reported. PDC residing in non-lymphoid tissue – such as the airways 24 and the liver 25 – exert a critical role in steady state by regulating mucosal immunity and maintaining tolerance to inhaled or ingested antigens 26 .…”
Section: The Innate Immune Functions Of Plasmacytoid Dendritic Cellsmentioning
confidence: 99%
“…Finally, PDC are also present in the thymus during homeostatic conditions, where they play a role in central tolerance 2729 . In contrast, during infections or autoimmune diseases, PDC migrate to inflamed lymph nodes 14 or inflamed epithelia 14, 23, 30 . The microenvironment in which PDC are present may influence oxygen and nutrient availability, which impacts on metabolic pathways (see section 3).…”
Section: The Innate Immune Functions Of Plasmacytoid Dendritic Cellsmentioning
confidence: 99%
“…Imiquimod's dual role: controlling "attraction" and "activation" The pattern of pDC migration reflects a complex interchange between chemokine receptor expression by pDCs and chemokine secretion in lymph nodes and inflamed tissues (14). In blood, pDCs, either constitutively or following activation, express CCR7 and respond to CCL21 in high endothelial venules, allowing them to home to lymph nodes.…”
Section: Ccl2 Is It Bad or Is It Good?mentioning
confidence: 99%
“…This pattern of pDC migration is consistent with the concept that pDCs become activated in a sequential fashion. Besides CCL2, imiquimod induces the production of the chemokine ligands for CXCR3 (15) and the skin-homing chemokine CCL20 (14). A recent study suggested that upregulation of CCR6 and CCR10 (the receptors for CCL20 and CCL27/28) on pDCs is crucial for imiquimod-dependent pDC migration to the skin (14), although the relevance of CCL20 and whether CCR6-expressing pDCs acquire a killer phenotype was not investigated in the model studied by Drobits et al Tumors including melanomas also produce chemokines that attract pDCs (16), but these may not activate their antitumor potential.…”
Section: Ccl2 Is It Bad or Is It Good?mentioning
confidence: 99%